RADI-14. FRAMELESS STEREOTACTIC RADIOSURGERY ON THE GAMMA KNIFE ICON: EARLY EXPERIENCE FROM 42 PATIENTS WITH BRAIN METASTASES. (12th August 2019) - Vulpe, Horia; Save, Akshay; Xu, Yuanguang; Elliston, Carl; Garrett, Matthew; Wu, Cheng-Chia; Cheng, Simon; Jani, Ashish; Bruce, Jeffrey; McKhann, Guy; Sisti, Michael; Wang, Tony
Abstract: BACKGROUND: The Gamma Knife (GK) Icon uses a Cone-Beam CT (CBCT) scanner and an infrared camera system to support the delivery of frameless radiosurgery. There are limited data on patients treated with frameless GK radiosurgery (GKRS) for brain metastases. OBJECTIVE: To describe the early experience, process, technical details, and short-term outcomes with frameless GKRS for brain metastases at our institution. METHODS: We describe our patient selection and workflow for frameless GKRS in detail. Because of the short interval of follow-up, we provide crude rates of local control. RESULTS: 42 patients had a total of 96 brain metastases. Median age was 69. 77 intact lesions were treated definitively, 18 cavities postoperatively, and 1 had GKRS for recurrence after resection. 11 patients underwent repeat GKRS to the same area. Median dose was 20Gy in 1 fraction (range: 14–21), 24Gy in 3 fractions (range: 19.5–27), and 25Gy in 5 fractions (Range: 25–30). Median treatment time was 23.7 minutes (Range: 7.3 – 85.5). 29 patients had a follow-up MRI in our records after completing GKRS. Median follow-up time was 105 days (Range: 16 – 314). 16 local recurrences (LR) were identified in 9 patients. An additional 6 patients had distant brain recurrence without LR. Crude mean time between GKRS and LR was 101 days (range 44–161 days). There were 6 patients with grade 1, 3 with grade 2, 2 with grade 3, and 1 with grade 4 toxicity. We found an improvement in workflow and a greater number of patients eligible for GKRS due to the ability to fractionate treatments. CONCLUSION: We report a large cohort of consecutive patients with brain metastases treated with frameless GKRS. We look forward to studies with longer follow-up to provide valuable data on clinical outcomes and to further our understanding of the radiobiology of hypofractionation in the brain.